Challenges and Solutions for Transplantation in Northeast India: Proceedings of the National Organ and Tissue Organization Session at the India Society of Organ Transplantation 2023 Meeting in Kolkata - Vivek B. Kute, MD, FRCP; Anil Kumar, MD; Awadhesh Kumar Yadav, MS; Shiny Suman Pradhan, MBBS; Sumana Arora, MD; Avinash Sunthlia, MD; Indakiewlin Kharbuli, MD; Guliver Potsangbam, MD; Manjuri Sharma, MD; Malsawmkima Chhakchhuak, MD; Samaresh Paul, MD; Sourabh Sharma, MD; et al. (Transplantation Direct)
Background:. India is the third highest in terms of the total number of organ transplants in a year worldwide mainly based on living donor transplants. The number of deceased donor transplants has been limited in India ranking only at the 68th position of 94 countries that reported data to Global Observatory on Organ Donation and Transplantation during the year 2022. Methods:. Representatives of National Organ and Tissue Transplant Organisation in addition to local transplant experts from Northeast India and Indian Society of Organ Transplantation discussed challenges and potential solutions for organ transplantation in Northeast India at the National Organ and Tissue Transplant Organisation session during the India Society of Organ Transplantation 2023 annual conference held at Kolkata. Results:. Here, we summarize deliberations on the opportunities for the care of patients with end-stage-organ failure in India with a focus on the Northeast part of the country. States in the Northeast face many problems for establishing organ transplant programs including but not limited to difficult terrain, lack of skilled healthcare providers (qualified doctors, nursing staff, and technicians) needed for dialysis and organ transplants, financial constraints, administrative issues, limited infrastructure in both government and private hospitals and, in addition, history of lacking support by professional societies. Discussions focused on establishing organ retrieval centers, minimal criteria for starting an organ transplant center, guidelines on how to start a new State Organ and Tissue Transplant Organization, establishing retrieval and transplant centers with support from National Organ Transplant Program, recent reforms in organ donation and transplantation, in addition to overcoming medical, surgical, immunological, administrative, sociocultural, geographic/regional challenges for organ transplantation in Northeast India. Conclusions:. Overall, deliberations aimed at providing a basis for policy makers to start and expand organ transplantation in low and low- to-middle income and infrastructurally poor states.